Sharia, State, and Family: Towards a Responsive Legislative Design for Household Resilience in Indonesia - Roihanah, Rif'ah; Rokamah, Ridho; Mufidah, Lailatul (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2026)
The family constitutes a fundamental social institution that undergirds the stability of both society and the state. In the context of rapid transformations driven by digitalization, modernization, and globalization, families in Indonesia face multifaceted challenges, including rising divorce rates, domestic violence, the erosion of parental roles, and a decline in the quality of family interactions. This study seeks to develop a responsive legislative model aimed at enhancing family resilience. It critically examines key regulatory instruments within Indonesian family law—specifically, the Marriage Law, the Compilation of Islamic Law, the Law on the Elimination of Domestic Violence, the Child Protection Law, and the Law on Population and Family Development—to conduct a normative evaluation of their responsiveness to evolving family dynamics. Utilizing normative juridical methods grounded in a literature review, the research employs the responsive legal theories of Nonet and Selznick, alongside the maqāṣid al-sharī'ah (objectives of Islamic law) framework, as analytical tools. The findings highlight the significance of adaptive and participatory regulation in safeguarding family rights and functions. Theoretically, enhancing family resilience in Indonesia requires the evolution of the legal framework toward a responsive model that integrates procedural norms with the values of justice, compassion, and shared responsibility.